Outcomes of temporalis muscle-based facial reanimation surgery: A systematic review and meta-analysis - Zhen Yu Wong; Frank W. de Jongh; Koen J.A.O. Ingels; Niels van Heerbeek; Sjaak Pouwels (JPRAS Open)
ABSTRACT: Background: Despite the encouraging findings of temporalis muscle-based facial reanimation surgery without the need for nerve grafting, there is a need for comprehensive evaluation of the impact of temporalis-based facial reanimation surgery on key outcome measures. Methods: Comprehensive search in Medline and Embase databases were carried out up to 25 February 2023. The articles that examined facial reanimation surgery using the temporalis muscle were included in this study. Postoperative changes in smile excursion and the angle of the mouth while smiling were pooled using the DerSimonian and Laird random-effects model. Narrative synthesis was conducted for other outcomes including assessments of spontaneous smile, subjective evaluation of facial symmetry using validated rating tools, functional outcomes, aesthetic outcomes and patient-reported outcomes owing to heterogeneity in reporting of the outcomes. Results: Twenty-four studies were included in the analysis. Conflicting evidence was demonstrated regarding emotional smile outcomes and its definition. The pooled changes in smile excursion postsurgery were 7.06 mm (95% CI: 3.73-10.40, P < 0.001; I2 = 0%) and the angle of the mouth were 11.76° (95% CI: 8.80-14.71, P < 0.001; I2 = 0%). Significant improvement was reported across the validated rating scales of symmetry, functional outcomes, aesthetic outcomes and patient-reported outcomes whereas the superiority compared to other procedures remained inconclusive. Conclusion: Overall, temporalis-based facial reanimation surgery is a promising option for addressing the negative effects of facial nerve paralysis on the patients’ quality of life. This study highlights the uncertainty surrounding the technique and need for further studies.